Martha Nussbaum's Feminist Philosophy on Body Autonomy and Its Relationship to the Experiences of Women Survivors of Child Marriage: A Case Study in Sukamara, Central Kalimantan. - Munte, Alfonso; Korsina, Riam Esobio (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2022)
This paper traces the journey of women who survived child marriage in Sukamara, Central Kalimantan. Sukamara is the district in Central Kalimantan with the highest child marriage rate. Central Kalimantan is one of the provinces with the highest child marriage rate in Indonesia. The purpose of this research how to analize experiences of survivors of child marriage victims regarding bodily autonomy. Then, the writer connects the autonomy of the body with the moral problematic phenomenon of objectivity as a power relation according to Martha Nussbaum's understanding. Researchers used interview research methods. The research instrument uses a detailed list and then is classified into factual solids, categories and theme questions. The results of the study, the research subjects experienced bitter experiences which were illustrated by acts of sexual violence, neglect from husbands and in-laws, and the lack of reproductive health due to women's responsibilities from power relations in survivors of child marriage. In addition, this study also confirmed Martha Nussbaum's theory that objectification is present in the absence of approval, pride and independence which is something negative.